Relative Temperature Maximum in Wound Infection and Inflammation as Compared with a Control Subject Using Long-Wave Infrared Thermography - Chanmugam, Arjun; Langemo, Diane; Thomason, Korissa; Haan, Jaimee; Altenburger, Elizabeth A; Tippett, Aletha; Henderson, Linda; Zortman, Todd A (Advances in skin & wound care, 2017)
The purpose of this retrospective case series was to determine whether a long-wave infrared thermography (LWIT, or thermal imaging) camera can detect specific temperature changes that are associated with wound infection and inflammation as compared with normal control subjects with similar anatomical wound locations. A retrospective, observational, collective, multiple case series of patients who underwent digital and thermal imaging of wounds in various states. The subjects were selected from multiple sites including an outpatient wound care clinic, a wound care physician's office, a rehabilitation hospital, and a home healthcare organization. Six subjects were selected for inclusion, including 2 each for the infection, inflammation, and normal control groups. The study collected relative temperature maximums as obtained and recorded by LWIT and digital imaging. In this case series, the authors demonstrate the use of an FDA-approved Scout (WoundVision, Indianapolis, Indiana) dual-imaging long-wave infrared and digital cameras to analyze images of wounds. In the 2 cases with clinically diagnosed wound infection, LWIT showed an elevation of temperature as evidenced by a maximum temperature differential between the wound and healthy skin of +4° C to 5° C. Also, LWIT was able to identify relative thermal changes of +1.5° C to 2.2° C in subjects presenting with clinical signs of inflammation. In addition, LWIT was able to show that the normal control subjects without diagnosis of infection or signs of inflammation had relative temperature differentials of +1.1° C to 1.2° C. Finally, LWIT could detect adequate treatment of infected wounds with antibiotics as evidenced by a return to normal temperature differences gradient of +0.8° C to 1.1° C, as compared with normal control subjects with wounds in the same anatomical location. Long-wave infrared thermography can collect and record objective data, including relative temperature maximums associated with infection, inflammation, and normal healing wounds.